¿La pandemia ha cambiado la metodología de entrenamiento del fútbol? (Has the pandemic changed soccer training methodologies?) - Sanmiguel-Rodríguez, Alberto; García-Soidán , José Luis; Navarro-Patón , Rubén (Retos, 2024)
Introducción. La pandemia de la covid-19 afectó directamente al mundo del deporte. Esto obligó a los cuerpos técnicos de los distintos clubes a reinventarse en sus procesos formativos con el fin de evitar la pérdida de rendimiento deportivo de sus plantillas, adaptando sus metodologías de entrenamiento a las condiciones que prevalecían en cada momento. Por tanto, el objetivo de esta investigación ha sido conocer si existen cambios en los modos de formación y planificación de los entrenadores de fútbol durante y después de la pandemia. Métodos: Para este trabajo se realizó un estudio descriptivo transversal en una muestra conformada por 517 entrenadores de diferentes divisiones y nacionalidades. Para caracterizar la muestra se utilizaron medidas descriptivas y se utilizó el chi-cuadrado de Pearson para estudiar si existe relación entre las variables estudiadas. Todos los análisis estadísticos se realizaron con Stata versión 12 (StataCorp., Estados Unidos) y la significación estadística siempre se estableció con un valor de p < 0,05. Resultados: Los resultados de este estudio indicaron que, independientemente de la división en la que desarrollaban su profesión, los entrenadores se vieron obligados a realizar cambios metodológicos y modificaciones sustanciales en la planificación de las sesiones. Evitaron ejercicios de contacto y se centraron en aspectos tácticos y psicológicos durante y desde la pandemia. Conclusión: Los resultados de este estudio pueden ser de gran utilidad para futuros organismos técnicos a la hora de distribuir formación y carga de trabajo. Palabras clave: fútbol; metodología; entrenamiento; entrenadores; pandemia; COVID-19 Abstract. Introduction. The covid-19 pandemic affected the world of sports very directly. This forced the coaching staffs of the different clubs to reinvent themselves in their training processes in order to avoid the loss of sports performance of their squads, adapting their training methodologies to the conditions that prevailed at all times. Therefore, the objective of this research has been to find out if there are changes in the training and planning modes of soccer coaches during and after the pandemic. Methods: For this work, a cross-sectional descriptive study was carried out in a sample made up of 517 coaches from different divisions and nationalities. To characterize the sample, descriptive measures were used and Pearson’s chi-square was used to study whether there is a relationship between the variables studied. All statistical analyses were performed with Stata version 12 (StataCorp., United States) and statistical significance was always established at a p value < 0.05. Results: The results of this study indicated that, regardless of the division in which they developed their profession, the coaches were forced to make methodological changes and substantial modifications in the planning of the sessions. They avoided contact exercises and focused on tactical and psychological aspects during and since the pandemic. Conclusion: The results of this study can be very useful for future technical bodies when it comes to distributing training and workload. Keywords: soccer; methodology; training; coaches; pandemic; COVID-19 Abstract. Introduction. The covid-19 pandemic affected the world of sports very directly. This forced the coaching staffs of the different clubs to reinvent themselves in their training processes in order to avoid the loss of sports performance of their squads, adapting their training methodologies to the conditions that prevailed at all times. Therefore, the objective of this research has been to find out if there are changes in the training and planning modes of soccer coaches during and after the pandemic. Methods: For this work, a cross-sectional descriptive study was carried out in a sample made up of 517 coaches from different divisions and nationalities. To characterize the sample, descriptive measures were used and Pearson’s chi-square was used to study whether there is a relationship between the variables studied. All statistical analyses were performed with Stata version 12 (StataCorp., United States) and statistical significance was always established at a p value < 0.05. Results: The results of this study indicated that, regardless of the division in which they developed their profession, the coaches were forced to make methodological changes and substantial modifications in the planning of the sessions. They avoided contact exercises and focused on tactical and psychological aspects during and since the pandemic. Conclusion: The results of this study can be very useful for future technical bodies when it comes to distributing training and workload. Keywords: soccer; methodology; training; coaches; pandemic; COVID-19